Effect of Preparation Conditions on the Characteristics of Hydroxypropyl Tapioca Starch - Haryadi Haryadi; Kapti R Kuswanto; B Ari Marwanti (Indonesian Food and Nutrition Progress, 1994)
Hydroxypropyl derivatives of tapioca starch with molar substitution of 0.000 – 0.113 were prepared by varying alkalinity of the reaction mixtures and propylene oxide used. Pasting behaviour and paste properties of the starches were evaluated. The results suggested that alkalinity facilitated derivatization, but using aqueous NaOH solution with molarity higher than 0.375 along with propylene oxide higher than 0.09375 ml per g starch was unfeasible. The hydroxypropylation procedures reduced the pasting temperature and maximum consistency temperature, but increased in swelling power of the granular starches, viscosity and stability of the starch pastes.